Toward Developing a Framework for Standardizing the Functional Assessment and Performance Evaluation of Assistive Robotic Manipulators (ARMs). (September 2015) - Velez, Jonathan; Ka, Hyun; Ding, Dan
The research and development of assistive robotic manipulators (ARMs) aims to enhance the upper-extremity daily functioning of individuals with disability. Resources continue to be invested, yet the field still lacks a standard framework to serve as a tool for the functional assessment and performance evaluation of ARMs. A review of the literature lends several suggestions from research in occupational therapy, rehabilitation robotics, and human-robot interaction. Performance assessments are often used during rehabilitation intervention by occupational therapists to evaluate a client's functional performance. Similarly, such assessments should be developed to make predictions regarding how ARM performance in a clinical setting may generalize to task execution throughout daily living. However, ergonomics and environmental differences have largely been ignored in past research. Additional insights from the literature provide suggestions for a common set of coding definitions, and a framework to organize the ad hoc performance measures observed across ARM studies.